Simulated electron energy loss spectra from a C70 crystal. - Nicholls, R; Nguyen-Manh, D; Cockayne, D (2006)
Electron energy loss spectra are simulated for a C70 crystalline structure. It is found that the simulated spectrum is similar to the unoccupied density of states of a C70 molecule, indicating that the crystalline structure has only a small effect on the spectrum. Unlike the case of a single molecule, however, the main contribution to the second peak in the spectrum cannot be ascribed as being due to the equatorial atoms.